EVALUATION OF LEARNING CURRICULUM IMPLEMENTATION DURING THE COVID-19 PANDEMIC - Shuhaibah SHUHAIBAH; Suryadi SYARIF; Ihsana El Khuluqo (Journal of Education and Leadership in Education, 2022)
Evaluation of the Implementation of the Learning Curriculum During the Covid-19 Pandemic at Peninggilan 3 Public Elementary School, Ciledug District, Tangerang City. The research aims to evaluate the implementation of curriculum implementation during the Covid-19 pandemic at Peninggilan 3 Public Elementary School through Distance Learning (PJJ) seen from the evaluation of context, input, process, and product, as well as Letters Ministerial Circular Number 4 of 2020 concerning the Implementation of Educational Policies in the Emergency Period for the Spread of Corona Virus Disease (Covid-19). The method used in this research is descriptive qualitative and CIPP evaluation (Context, Input, Process, and product). The implementation of the learning curriculum during the Covid-19 pandemic was developed referring to the national curriculum whose implementation was carried out online through google classroom, google meet, zoom meeting, and whatsapp group described in the Education Unit Level Curriculum (KTSP). Difficulties and obstacles in implementing the learning curriculum for teachers during the Covid-19 pandemic can be overcome by participating in training in the field of Information and Technology, such as: making video media, models, and learning methods that are appropriate to the Covid-19 pandemic, so that teachers can make their own learning videos according to the student's character and eliminate student boredom in the PJJ process. PJJ clearly has positive and negative impacts on students, therefore assistance and parental participation are needed, especially in mastering scientific disciplines, assertiveness in controlling and using children's gadgets at home, as well as good communication between teachers and parents.